Outcome assessment of intraoperative radiotherapy for brain metastases: results of a prospective observational study with comparative matched-pair analysis - Layer, Julian; Hamed, Motaz; Potthoff, Anna-Laura; Dejonckheere, Cas S.; Layer, Katharina; Sarria, Gustavo R.; Scafa, Davide; Koch, David; Köksal, Mümtaz; Kugel, Fabian; Grimmer, Molina; Holz, Jasmin A.; et al. (Journal of neuro-oncology, 2023)
Intraoperative radiation therapy (IORT) is an emerging alternative to adjuvant stereotactic external beam radiation therapy (EBRT) following resection of brain metastases (BM). Advantages of IORT include an instant prevention of tumor regrowth, optimized dose-sparing of adjacent healthy brain tissue and immediate completion of BM treatment, allowing an earlier admission to subsequent systemic treatments. However, prospective outcome data are limited. We sought to assess long-term outcome of IORT in comparison to EBRT.
Online veröffentlicht: 21. Juli 2023
Gesehen am 21.02.2024